Pelaksanaan Rencana Pembangunan Berkelanjutan (Studi pada Kampung Inggris Pare Kabupaten Kediri) - Wicaksono, Moh. Sony (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
This study aimed to analyze the implementation of the sustainable development plan in Kampung Inggris Pare Kediri Regency which focuses on social equity, economic, and environmental. This study uses data collection techniques such as interviews, observation, and documentation. The results of implementation of sustainable social development is the Regional Development Planning Department conducting development studies in Kampung Inggris, by forming Brigadier Kampung Inggris to maintain social order. In the field of sustainable economic Culture and Tourism Department from carrying out the promotion of culture and tourism. In the field of environmental sustainability, Environment Department, conducting coaching waste management and community-based sanitation program. The construction plan has not been coordinated between departments, so it is necessary to establish working group on education to improve the distribution of social, economic, and environmental.